Wage drift and error correction: Evidence from Finland - Timo Tyrväinen (Bank of Finland, 1992)
This article examines the process which generates wage increments in excess to those agreed upon collectively, Le. wage drift. A synthesis of the explanations common in the literature is sketched. This attempt has been strongly motivated by the notion that the time series properties of the wage series of interest differ significantly from each other. This has led us to consider wage drift as dynamics related to adjustment towards an equilibrium defined in terms of cointegrating relations. Empirical results are in accordance with the error correction hypothesis proposed. There is a robust inverse correlation between the contract wage and wage drift. The adjustment is quite rapid but not instantaneous. Wage drift tends to be larger when the dispersion of financial prospects as foreseen by the firms - measured by the standard deviation of the stock of orders - is large. Wage drift is positively correlated with changes in the demand for labour. Finally, the variation in wage drift appears to be correlated with errors in (inflation) expectations.
URN:NBN:fi:bof-201808021868
Keywords: 330